A Colossal Enhancement of Thermoelectric Performance of Monolayer SbAs Using Strain Engineering. Issue 8 (25th June 2021) - Liu, Lu; Peng, Chengxiao; Feng, Zhenzhen; Yan, Yuli; Zhang, Guangbiao; Wang, Chao; Zhang, Peiyu; Gu, Qinfen
Abstract : The effect of uniaxial strain on the thermoelectric (TE) conversion efficiency of puckered monolayer arsenic antimonide (SbAs) is explored based on the density function and Boltzmann transport equation (BTE) theories. The lattice thermal conductivity ( κ l ) can be sharply lowered through tensile strain. Taking a + 3.25% tensile strain as an example, κ l along the armchair (AC) direction at 300 K decreases almost three times than that without a strain, which is ascribed to the low phonon group velocity, large Grüneisen parameter, and high three‐phonon scattering phase space. The carrier effective mass decreases in imposing tensile strain monolayer SbAs and slightly suppresses the Seebeck coefficient; however, the electrical conductivity is improved due to the small effective mass and long relaxation time. Thus, power factor increases by 3.4 times under a  + 3.25% tensile at n = 8.3 × 10 11 cm −2 compared with a SbAs monolayer without strain. Thereafter, the figure of merit in an n‐type SbAs monolayer with a tensile strain of +3.25% is eight times as large as that in SbAs without strain at 300 K along the AC direction. Furthermore, the maximum TE figure of merit is 1.85 for an n‐type SbAs monolayer with +3.25% strain at 800 K. This study paves a way toward improving the TE performance through strain engineering in the TE field. Abstract : When a small tensile strain is applied along the AC direction, the figure of merit (ZT) of an n‐type SbAs monolayer shows remarkable enhancement due to the improvement of power factor and the suppression of phonon transport.